Analysis and verification of electrodynamic force, thermal stress and current sharing for CRAFT converter structure design - WANG, Zhongma; SHI, Chaoyi; ZHANG, Xiuqing; LU, Wenwu; ZHANG, Sheng; GAO, Xianhe; XU, Tao; SHAO, Xingxing; HUANG, Liansheng (Plasma science & technology, 2024)
In the design realm of fusion power supplies, structural components play a pivotal role in ensuring the safety of fusion devices. To verify the reliability of the converter structure design at the Comprehensive Research Facility for Fusion Technology (CRAFT), meticulous analysis of the converter's dynamic impact is carefully performed based on the worst fault current (400 kA), firstly. Subsequently, the thermal stress analysis based on the maximum allowable steady-state temperature is finished, and the equivalent thermal stress, thermal deformation, maximum shear stress of a single bridge arm and the whole converter are studied. Furthermore, a simple research method involving the current-sharing characteristics of a bridge arm with multi-thyristor parallel connection is proposed using a combination of Simplorer with Q3D in ANSYS. The results show that the current-sharing characteristics are excellent. Finally, the structural design has been meticulously tailored to meet the established requirements.